Legal Protection for Consumers in Sharia Insurance in Indonesia - Indrawanto, Setya; Hermansyah, Yus; Badruzaman, Dudi; Nuralam, Ikhsan (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
Legal protection for consumers in Sharia insurance in Indonesia is very important to ensure that transactions and services provided by Sharia insurance companies are run by sharia principles and provide fairness and security for consumers. The research method used is library research with a qualitative approach. Data was collected through observation and documentation, with qualitative analysis data analysis. The results of the study show that sharia insurance in Indonesia not only provides financial protection benefits for individuals and families, but also promotes the values of social justice, solidarity, and sustainable economic development in accordance with sharia principles. Sharia insurance is not only an important financial choice for Muslim consumers but also has a positive impact in strengthening the financial security of individuals and society more broadly, by upholding sharia values.